Anti-aging cable and preparation method thereof
By using a blend made of modified graphene and conductive alloy as the cable insulation layer and the sheath layer, and performing radio frequency plasma treatment, the problem of water branches of XLPE power cable is solved, and the thermal stability of the cable is achieved. Improved resistance to water tree aging.
Patent Information
- Application Number
- CN202411573266.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-11
AI Technical Summary
Existing XLPE power cables are prone to aging of water branches during operation, resulting in the formation of electric branches and breakdown of insulating structures, affecting the service life and operating reliability of the cable.
A blend made of modified graphene, polyimide and linear low-density polyethylene is used as an insulating layer and a sheath layer to coat the wire core and wire made of conductive alloy, and radio frequency plasma is performed on the insulating layer. Body treatment is used to enhance the resistance to water tree aging.
Through the esterification reaction of modified graphene and the borylation treatment of conductive alloys, the thermal stability and water tree aging resistance of the cable are improved, the service life of the cable is extended and its operating reliability is improved.
Smart Images

Figure BDA0005121089770000091 
Figure BDA0005121089770000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cables, in particular to an anti-aging cable and a preparation method thereof. Background Art
[0002] With the continuous development and progress of science and technology, economy and industry, the development of my country's power and power grid industry is at the world's leading level. At the same time, my country's demand for electricity is also expanding, and power resources have become an important pillar of the existing energy industry. The safe and efficient transmission of electricity is one of the keys to its widespread application. Power cables have been used as power transmission line materials for more than a hundred years. They have the advantages of small footprint, low electromagnetic pollution, high power supply reliability and stable transmission performance.
[0003] With the continuous increase of power load, the electrical insulation structure of XLPE power cable will produce water dendrite aging phenomenon under the combined effect of electricity, heat, mechanics, moisture and other influencing factors during operation. Under the conditions of moisture and electrical stress, water dendrites continue to grow as the electric field action time increases. Although the growth process of water dendrites is particularly slow, it cannot immediately lead to the breakdown of the insulation layer of the power cable. However, studies have shown that with the further growth of water dendrites, under the continuous action of a higher AC electric field, the continuous concentration of the electric field at the tip of the water dendrite will not only lead to the formation of electrical dendrites at the tip of the water dendrites, but also may transform into electrical dendrites. Especially in the case of operating overvoltage caused by lightning or misoperation, the instantaneous overvoltage is enough to transform the water dendrites in the XLPE power cable into electrical dendrites. Once the electrical dendrites are formed, they will continue to grow. The electrical dendrites can cause the insulation structure of the XLPE power cable to be broken down in a very short time, resulting in the destruction of the insulation structure, which has a serious impact on the service life of the cable and the reliability of the cable operation, thus causing a power outage. Summary of the invention
[0004] The object of the present invention is to provide an anti-aging cable and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: an anti-aging cable, which is made of a blend of modified graphene, polyimide and linear low-density polyethylene as an insulating layer and a sheath layer to cover a core and a conductor made of a conductive alloy; there is also a shielding layer between the insulating layer and the sheath layer.
[0006] Furthermore, the modified graphene is firstly prepared by subjecting graphene oxide to carboxylation treatment and then grafting polyvinyl alcohol.
[0007] Furthermore, the conductive alloy is prepared by boronizing aluminum, then adding titanium and zirconium, and then subjecting the aluminum to ultrasonic treatment.
[0008] Furthermore, a method for preparing an anti-aging cable comprises the following preparation steps:
[0009] (1) Mixing graphene oxide with deionized water, ultrasonicating at 21kHz for 40 to 80 minutes, adding sodium hydroxide in an ice-water bath, stirring at 80 to 150 rpm for 30 minutes, adding chloroacetic acid, ultrasonicating at 21kHz for 1.5 to 3 hours, and then centrifugally washing with 1 mol / L dilute hydrochloric acid until the pH of the washing solution is 7 to 8, drying at -24 to -48°C for 25 to 40 hours, and then adding N,N-dimethylformamide, ultrasonicating at 21kHz for 40 to 80 minutes, adding polyvinyl alcohol 1799, and continuing ultrasonicating for 20 to 50 minutes, adding dicyclohexylcarbodiimide and 4-dimethylaminopyridine, stirring at 200 to 400 rpm for 60 to 80 hours, and then placing in a pretreatment dialysis bag for dialysis treatment for 3 to 5 days, replacing deionized water every 12 hours, and finally drying at -24 to -48°C for 25 to 40 hours to obtain modified graphene;
[0010] (2) Polyethylene DFDA-7042 and polyimide YS20 were mixed, heated to 330-360°C, stirred at 50-100 rpm for 10-40 min, modified graphene, tri-tert-butyl hydroxybenzoate, 2,5-dimethyl-2,5-bis(tert-butyl peroxide)-3-hexyne, and dibutyltin dilaurate were added, stirred for 15-60 min, allowed to stand for 3-6 h, and then heated at 80°C and vacuum for 10 min. -3 Degassing was performed under an environment of 20 minutes, and finally extrusion granulation was performed. The process parameters were as follows: screw diameter was 20 mm, aspect ratio was 25:1, and temperature was 320-400°C to obtain a blend;
[0011] (3) The aluminum ingot is heated to 750-770°C, and A1-3B master alloy and boron powder are added for boronization. The ingot is stirred at 50-100 rpm for 30-80 min, and the temperature is kept for 10-30 min. The upper two-thirds of the melt is taken, and sponge zirconium and sponge titanium are added. The vacuum degree is drawn to 4.6×10 -3 Pa, then fill with argon to 50MPa, under the state of vibration frequency of 38-50Hz, this vibration state continues until the casting step, heat up to 1900-2200℃ at 5-13℃ / min, keep warm for 5-10min, press hexachloroethane into the bottom of the molten metal to stir, degas and slag, then remove the surface scum, cast the mold, cool and shape, and obtain the conductive alloy;
[0012] (4) The conductive alloy is drawn into a wire with a diameter of 0.1 to 0.7 mm, coated with the blend with a thickness of 1 to 2 mm, subjected to radio frequency plasma treatment, and then covered with a shielding layer woven of copper wire with a thickness of 0.5 to 2 mm and a protective layer with a thickness of 2 to 5 mm to obtain an anti-aging cable.
[0013] Furthermore, the preparation method of the pretreatment dialysis in step (1) is as follows: a dialysis bag with a molecular weight cutoff of 12,000 is placed in deionized water at 95° C. and boiled for 10 minutes.
[0014] Furthermore, in step (1), the mass ratio of graphene oxide, deionized water, sodium hydroxide, chloroacetic acid, N,N-dimethylformamide, polyvinyl alcohol 1799, dicyclohexylcarbodiimide, and 4-dimethylaminopyridine is 1-3:500-1000:50:50:50-80:4-16:0.08-0.18:0.01.
[0015] Furthermore, in step (2), the mass ratio of polyethylene DFDA-7042, polyimide YS20, modified graphene, tri-tert-butyl hydroxybenzoate, 2,5-dimethyl-2,5-bis(tert-butyl peroxide)-3-hexyne, and dibutyltin dilaurate is 100:5-20:0.1-0.8:0.05:0.05-0.1:0.04-0.2.
[0016] Furthermore, in step (3), the mass ratio of the aluminum ingot, the A1-3B master alloy, the boron powder, the zirconium sponge and the titanium sponge is 10:0.1-0.3:0.03:0.2-1:0.1.
[0017] Furthermore, the process parameters of the RF plasma in step (4) are: oxygen gas, flow rate of 0.04-0.1 L / min, gas pressure of 15-20 Pa, and power of 150-250 W.
[0018] Furthermore, the protective layer in step (4) is made of the blend prepared in step (2).
[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0020] The cable of the invention is prepared by coating a core and a conductor made of a conductive alloy with a blend made of modified graphene, polyimide and linear low-density polyethylene as an insulation layer and a sheath layer, so as to achieve the effects of thermal stability and resistance to water tree aging.
[0021] First, graphene oxide is carboxylated under strong alkaline conditions, and then the hydroxyl group of polyvinyl alcohol and the carboxyl group of graphene are esterified to enhance the dispersion of graphene in the matrix, and then mixed with polyimide in a linear low-density polyethylene matrix. The introduction of nanoparticles improves the compatibility between the two polymer materials and can occupy the holes in the matrix, filling the original free volume gaps, reducing the free volume of the blend, making the structure more stable, and hindering the thermal motion of the polyethylene molecular chain, thereby enhancing the mechanical properties of the cable. At the same time, by enhancing the low expansion performance of the matrix, the sub-microscopic air gaps for water to enter are reduced, thereby reducing the probability of inducing water dendrites, and the linear low-density polyethylene The short branches on the molecular chain of ethylene form a large number of entangled molecular chain structures after cross-linking. It is not easy to form water-filled holes under the action of the electric field, which inhibits the further development of water tree branches. Then, the core and wire made of conductive alloy are coated as insulating materials and sheath materials. The insulating layer is treated with coupled plasma, and active particles such as ions, electrons and free radicals are generated by excitation and dissociation of oxygen molecules. A large number of polar oxygen-containing groups are generated on the surface of the matrix to contact the non-polar air environment, and then the surface chemical composition is reconstructed, so that the matrix can overcome the higher diffusion activation energy at a higher aging temperature. After the cable has been working for a long time, the surface hydrophobicity is achieved through the insulating layer, thereby enhancing the cable's resistance to water tree aging.
[0022] The conductive alloy uses aluminum as a conductive matrix. The aluminum is first borated to ensure the conductive properties of the alloy. The aluminum-boron compound reacts with the transition metal elements in the melt to generate corresponding borides, which transform the solid solution state into a precipitation state and precipitate to the bottom of the melt, thereby reducing the damage of the solid solution alloying elements to the conductivity. Titanium and zirconium are then dispersed in the matrix as the second phase to form a solid solution. Under high temperature conditions, the boron element is completely dissolved in the liquid matrix and forms a single liquid phase. During the solidification process, part of the boron element generates boron-titanium alloy and boron-zirconium alloy, which gradually precipitates and grows from the liquid phase. That is, during the solidification process, the boron element will be enriched at the front of the solid-liquid interface, causing the composition to The supercooling phenomenon leads to the refinement of grains and reduces the thermal expansion of the alloy matrix, thereby improving the cable's resistance to water tree aging. Then, the cavitation effect caused by vibration makes the alloy's atoms move more violently and fully during the smelting process, so that the components in the alloy diffuse evenly, thereby further improving the alloy's mechanical properties. Then, during the alloy pouring step, the gas inside the molten alloy is discharged through vibration, eliminating defects such as holes in conventional casting, thereby improving the alloy's mechanical properties and intensifying the movement of the alloy during solidification, which helps to refine the grains of wire and cable alloys and eliminate defects such as holes, thereby enhancing the alloy's mechanical properties and the cable's resistance to water tree aging. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the anti-aging cables prepared in the following examples are as follows:
[0025] Water tree resistance: The same size of the embodiment and the comparative example were taken according to ASTM D6097a, and water tree resistance was tested, which was expressed by water tree growth resistance RWTG; then a cable with a length of 500 mm was cut, and the insulation layer with a length of 20 mm at one end was removed as a high-voltage terminal, and then the outer semi-conductive layer with a length of about 100 mm at both ends of the cable was stripped off and polished smooth, and the middle 280 mm area was used as a water tree aging area, and a needle with a needle tip curvature radius of 2.5 μm was used to pierce a needle hole with a depth of 1.5 mm every 4 mm in the aging area, and the aging area was covered with a heat shrink tube, and a sodium chloride solution with a concentration of 0.1 mol / L was added thereto. After 30 days of water tree aging, the water tree resistance test was performed again.
[0026] Thermal stability: The high temperature resistance effect of the embodiment and the comparative example of the same size was tested. After being placed at 150°C for 100 hours, the tensile strength and elongation at break were tested in accordance with GB / T1040.
[0027] Conductive performance: Take the embodiment and comparative example GB / T3048.2 of the same size, use QJ36S-2 DC low resistance tester to measure the resistance value of the sample, and then convert the resistance into conductivity, and determine the resistivity of international annealed copper as 0.017241 as 100% IACS, and test the conductivity of the sample.
[0028] Example 1
[0029] (1) A dialysis bag with a molecular weight cutoff of 12,000 was placed in deionized water at 95°C and boiled for 10 minutes to obtain a pretreated dialysis bag; graphene oxide was mixed with deionized water, ultrasonicated at 21kHz for 40 minutes, sodium hydroxide was added in an ice water bath, stirred at 80rpm for 30 minutes, chloroacetic acid was added, ultrasonicated at 21kHz for 1.5 hours, and then centrifuged and washed with 1 mol / L dilute hydrochloric acid until the pH of the washing solution was 7, dried at -24°C for 25 hours, and then N,N-dimethylformamide was added, ultrasonicated at 21kHz for 40 minutes, and polyvinyl alcohol was added. 799, continue ultrasonication for 20 minutes, add dicyclohexylcarbodiimide and 4-dimethylaminopyridine, stir at 200rpm for 60 hours, then place in a pre-treated dialysis bag for dialysis treatment for 3 days, replace deionized water every 12 hours, and finally dry at -24°C for 25 hours to obtain modified graphene; the mass ratio of graphene oxide, deionized water, sodium hydroxide, chloroacetic acid, N,N-dimethylformamide, polyvinyl alcohol 1799, dicyclohexylcarbodiimide, and 4-dimethylaminopyridine is 1:500:50:50:50:4:0.08:0.01;
[0030] (2) Polyethylene DFDA-7042 and polyimide YS20 were mixed, heated to 330°C, stirred at 50 rpm for 10 min, modified graphene, tri-tert-butyl hydroxybenzoate, 2,5-dimethyl-2,5-bis(tert-butyl peroxide)-3-hexyne, and dibutyltin dilaurate were added, stirred for 15 min, allowed to stand for 3 h, and then heated at 80°C and vacuum for 10 min. -3 Degassing is performed under an environment of 20 minutes, and finally extrusion granulation is performed. The process parameters are as follows: the screw diameter is 20 mm, the aspect ratio is 25:1, and the temperature is 320°C to obtain a blend; the mass ratio of the polyethylene DFDA-7042, the polyimide YS20, the modified graphene, tri-tert-butyl hydroxybenzoate, 2,5-dimethyl-2,5-bis(tert-butyl peroxide)-3-hexyne, and dibutyltin dilaurate is 100:5:0.1:0.05:0.0.5:0.04;
[0031] (3) The aluminum ingot was heated to 750°C, and A1-3B master alloy and boron powder were added for boronization. The mixture was stirred at 50 rpm for 30 min and kept warm for 10 min. The upper two-thirds of the melt was taken and sponge zirconium and sponge titanium were added. The vacuum degree was reduced to 4.6×10 -3Pa, then filled with argon to 50MPa, under the state of vibration frequency of 38Hz, this vibration state continues until the casting step, the temperature is raised to 1900℃ at 5℃ / min, kept warm for 5min, hexachloroethane is pressed into the bottom of the molten metal to stir, degas and slag, then the surface scum is removed, the casting mold is cast, and the conductive alloy is obtained; the mass ratio of the aluminum ingot, A1-3B master alloy, boron powder, sponge zirconium and sponge titanium is 10:0.1:0.03:0.2:0.1;
[0032] (4) The conductive alloy is pulled into a wire with a diameter of 0.1 mm, coated with the blend to a thickness of 1 mm, and subjected to radio frequency plasma treatment with the following process parameters: oxygen gas, flow rate of 0.04 L / min, air pressure of 15 Pa, power of 150 W, and then covered with a shielding layer woven from copper wire with a thickness of 0.5 mm and a protective layer of the blend prepared in step (2) with a thickness of 2 mm, to obtain an anti-aging cable.
[0033] Example 2
[0034] (1) A dialysis bag with a molecular weight cutoff of 12,000 was placed in deionized water at 95°C and boiled for 10 minutes to obtain a pretreated dialysis bag; graphene oxide was mixed with deionized water, ultrasonicated at 21kHz for 60 minutes, sodium hydroxide was added in an ice water bath, stirred at 120rpm for 30 minutes, chloroacetic acid was added, ultrasonicated at 21kHz for 2 hours, and then centrifuged and washed with 1 mol / L dilute hydrochloric acid until the pH of the washing solution was 7.5, dried at -36°C for 32 hours, and then N,N-dimethylformamide was added, ultrasonicated at 21kHz for 60 minutes, and polyvinyl alcohol was added. 799, continue ultrasonication for 35 minutes, add dicyclohexylcarbodiimide and 4-dimethylaminopyridine, stir at 300rpm for 70 hours, then place in a pre-treated dialysis bag for dialysis treatment for 4 days, replace deionized water every 12 hours, and finally dry at -36°C for 32 hours to obtain modified graphene; the mass ratio of graphene oxide, deionized water, sodium hydroxide, chloroacetic acid, N,N-dimethylformamide, polyvinyl alcohol 1799, dicyclohexylcarbodiimide, and 4-dimethylaminopyridine is 2:750:50:50:65:10:0.12:0.01;
[0035] (2) Polyethylene DFDA-7042 and polyimide YS20 were mixed, heated to 340°C, stirred at 75 rpm for 25 min, modified graphene, tri-tert-butyl hydroxybenzoate, 2,5-dimethyl-2,5-bis(tert-butyl peroxide)-3-hexyne, and dibutyltin dilaurate were added, stirred for 40 min, allowed to stand for 5 h, and then heated at 80°C and vacuum for 10 min. -3Degassing is performed under an environment of 20 minutes, and finally extrusion granulation is performed. The process parameters are as follows: the screw diameter is 20 mm, the aspect ratio is 25:1, and the temperature is 360°C to obtain a blend; the mass ratio of the polyethylene DFDA-7042, the polyimide YS20, the modified graphene, tri-tert-butyl hydroxybenzoate, 2,5-dimethyl-2,5-bis(tert-butyl peroxide)-3-hexyne, and dibutyltin dilaurate is 100:13:0.4:0.05:0.08:0.12;
[0036] (3) The aluminum ingot was heated to 760°C, and A1-3B master alloy and boron powder were added for boronization. The mixture was stirred at 75 rpm for 50 min and kept warm for 20 min. The upper two-thirds of the melt was taken and sponge zirconium and sponge titanium were added. The vacuum degree was reduced to 4.6×10 -3 Pa, then filled with argon to 50MPa, under the state of vibration frequency of 41Hz, this vibration state continues until the casting step, the temperature is raised to 2100℃ at 8℃ / min, kept warm for 7min, hexachloroethane is pressed into the bottom of the molten metal to stir, degas and slag, then the surface scum is removed, the mold is cast, and the conductive alloy is obtained; the mass ratio of the aluminum ingot, A1-3B master alloy, boron powder, sponge zirconium and sponge titanium is 10:0.2:0.03:0.6:0.1;
[0037] (4) The conductive alloy is pulled into a wire with a diameter of 0.3 mm, coated with the blend to a thickness of 1.5 mm, and subjected to radio frequency plasma treatment with the following process parameters: oxygen gas, flow rate of 0.07 L / min, gas pressure of 18 Pa, power of 200 W, and then covered with a shielding layer woven from copper wire with a thickness of 1.4 mm and a protective layer of the blend prepared in step (2) with a thickness of 4 mm, to obtain an anti-aging cable.
[0038] Example 3
[0039] (1) A dialysis bag with a molecular weight cutoff of 12,000 was placed in deionized water at 95°C and boiled for 10 minutes to obtain a pretreated dialysis bag; graphene oxide was mixed with deionized water, ultrasonicated at 21kHz for 80 minutes, sodium hydroxide was added in an ice-water bath, stirred at 150 rpm for 30 minutes, chloroacetic acid was added, and ultrasonicated at 21kHz for 3 hours, and then centrifuged and washed with 1 mol / L dilute hydrochloric acid until the pH of the washing solution was 8, dried at -48°C for 40 hours, and then N, N-dimethylformamide was added, ultrasonicated at 21kHz for 80 minutes, and polyvinyl alcohol 179 was added. 9. Continue ultrasonication for 50 min, add dicyclohexylcarbodiimide and 4-dimethylaminopyridine, stir at 400 rpm for 80 h, then place in a pre-treated dialysis bag for dialysis treatment for 5 days, replace deionized water every 12 h, and finally dry at -48 ° C for 40 h to obtain modified graphene; the mass ratio of the graphene oxide, deionized water, sodium hydroxide, chloroacetic acid, N, N-dimethylformamide, polyvinyl alcohol 1799, dicyclohexylcarbodiimide, and 4-dimethylaminopyridine is 3:1000:50:50:80:16:0.18:0.01;
[0040] (2) Polyethylene DFDA-7042 and polyimide YS20 were mixed, heated to 360°C, stirred at 100 rpm for 40 min, modified graphene, tri-tert-butyl hydroxybenzoate, 2,5-dimethyl-2,5-bis(tert-butyl peroxide)-3-hexyne, and dibutyltin dilaurate were added, stirred for 60 min, allowed to stand for 6 h, and then heated at 80°C and vacuum for 10 min. -3 Degassing is performed under an environment of 20 minutes, and finally extrusion granulation is performed. The process parameters are as follows: the screw diameter is 20 mm, the aspect ratio is 25:1, and the temperature is 400° C. to obtain a blend; the mass ratio of the polyethylene DFDA-7042, the polyimide YS20, the modified graphene, tri-tert-butyl hydroxybenzoate, 2,5-dimethyl-2,5-bis(tert-butyl peroxide)-3-hexyne, and dibutyltin dilaurate is 100:20:0.8:0.05:0.1:0.2;
[0041] (3) The aluminum ingot was heated to 770°C, and A1-3B master alloy and boron powder were added for boronization. The mixture was stirred at 100 rpm for 80 min and kept warm for 30 min. The upper two-thirds of the melt was taken and sponge zirconium and sponge titanium were added. The vacuum degree was reduced to 4.6×10 -3Pa, then filled with argon to 50MPa, under the state of vibration frequency of 50Hz, this vibration state continues until the casting step, the temperature is raised to 2200℃ at 13℃ / min, kept warm for 10min, hexachloroethane is pressed into the bottom of the molten metal to stir, degas and slag, then the surface scum is removed, the casting mold is cast, and the conductive alloy is obtained; the mass ratio of the aluminum ingot, A1-3B master alloy, boron powder, sponge zirconium and sponge titanium is 10:0.3:0.03:1:0.1;
[0042] (4) The conductive alloy is pulled into a wire with a diameter of 0.7 mm, coated with the blend to a thickness of 2 mm, and subjected to radio frequency plasma treatment with the following process parameters: oxygen gas, flow rate of 0.1 L / min, gas pressure of 20 Pa, power of 250 W, and then covered with a shielding layer woven of copper wire with a thickness of 2 mm and a protective layer of the blend prepared in step (2) with a thickness of 5 mm, to obtain an anti-aging cable.
[0043] Comparative Example 1
[0044] The difference between Comparative Example 1 and Example 2 is that step (1) is omitted; the remaining steps are the same as those of Example 2.
[0045] Comparative Example 2
[0046] The difference between Comparative Example 2 and Example 2 is that there is no step (1), and step (2) is changed to: polyethylene DFDA-7042 and polyimide YS20 are mixed, the temperature is raised to 340°C, and stirred at 75 rpm for 25 min, tri-tert-butyl hydroxybenzoate, 2,5-dimethyl-2,5-bis(tert-butyl peroxide)-3-hexyne, and dibutyltin dilaurate are added, and stirring is continued for 40 min, and the mixture is allowed to stand for 5 h, and then heated at 80°C and vacuum degree of 10 -3 Degassing was carried out under an environment of 20 minutes, and finally extrusion granulation was carried out. The process parameters were as follows: the screw diameter was 20 mm, the aspect ratio was 25:1, and the temperature was 360°C to obtain a blend; the mass ratio of the polyethylene DFDA-7042, polyimide YS20, tri-tert-butyl hydroxybenzoate, 2,5-dimethyl-2,5-bis(tert-butyl peroxide)-3-hexyne, and dibutyltin dilaurate was 100:13:0.05:0.08:0.12; and the remaining steps were the same as in Example 2.
[0047] Comparative Example 3
[0048] The difference between Comparative Example 3 and Example 2 is that step (2) is different. Step (2) is changed to: polyethylene DFDA-7042, modified graphene, tri-tert-butyl hydroxybenzoate, 2,5-dimethyl-2,5-bis(tert-butyl peroxide)-3-hexyne, and dibutyltin dilaurate are mixed, heated to 340°C, stirred at 75 rpm for 40 min, allowed to stand for 5 h, and then heated at 80°C and vacuum for 10 -3 Degassing was carried out under an environment of for 20 min, and finally extrusion granulation was carried out, and the process parameters were as follows: the screw diameter was 20 mm, the aspect ratio was 25:1, and the temperature was 360°C to obtain a blend; the mass ratio of the polyethylene DFDA-7042, modified graphene, tri-tert-butyl hydroxybenzoate, 2,5-dimethyl-2,5-bis(tert-butyl peroxide)-3-hexyne, and dibutyltin dilaurate was 100:0.4:0.05:0.08:0.12; the remaining steps were the same as in Example 2.
[0049] Comparative Example 4
[0050] The difference between Comparative Example 4 and Example 2 is that step (4) is different. Step (4) is changed to: the conductive alloy is pulled into a wire with a diameter of 0.3 mm, and the wire is coated with the blend to a thickness of 1.5 mm, and then covered with a shielding layer woven from copper wire with a thickness of 1.4 mm and a protective layer of the blend prepared in step (2) with a thickness of 4 mm, to obtain an anti-aging cable; the remaining steps are the same as in Example 2.
[0051] Comparative Example 5
[0052] The difference between Comparative Example 5 and Example 2 is that step (3) is different. Step (3) is changed to: heating the aluminum ingot to 760°C, adding sponge zirconium and sponge titanium, and drawing the vacuum degree to 4.6×10 -3 Pa, and then filled with argon to 50MPa, under the state of vibration frequency of 41Hz, this vibration state continues until the casting step, the temperature is raised to 2100℃ at 8℃ / min, and kept warm for 7min, hexachloroethane is pressed into the bottom of the molten metal to stir, degas and slag, and then the surface scum is removed, the casting mold is cast, and the conductive alloy is obtained; the mass ratio of the aluminum ingot, sponge zirconium and sponge titanium is 10:0.6:0.1; the remaining steps are the same as those in Example 2.
[0053] Comparative Example 6
[0054] The difference between Comparative Example 6 and Example 2 is that step (3) is different. Step (3) is changed to: heating the aluminum ingot to 760° C., adding A1-3B master alloy and boron powder for boronization treatment, stirring at 75 rpm for 50 min, keeping warm for 20 min, taking the upper two-thirds of the melt, pressing hexachloroethane into the bottom of the molten metal with stirring to degas and slag, then removing the surface scum, casting the mold, cooling and shaping, and obtaining a conductive alloy; the mass ratio of the aluminum ingot, A1-3B master alloy, and boron powder is 10:0.2:0.03; the remaining steps are the same as Example 2.
[0055] Comparative Example 7
[0056] The difference between Comparative Example 7 and Example 2 is that step (3) is different. Step (3) is changed to: heating the aluminum ingot to 760°C, adding A1-3B master alloy and boron powder for boronization, stirring at 75 rpm for 50 min, keeping warm for 20 min, taking two-thirds of the melt, adding sponge zirconium and sponge titanium, and drawing the vacuum degree to 4.6×10 -3 Pa, then filled with argon to 50MPa, heated to 2100°C at 8°C / min, kept warm for 7min, pressed hexachloroethane into the bottom of the molten metal with stirring for degassing and slagging, then removed the surface scum, cast the mold, cooled and shaped to obtain a conductive alloy; the mass ratio of the aluminum ingot, A1-3B master alloy, boron powder, sponge zirconium and sponge titanium was 10:0.2:0.03:0.6:0.1; the remaining steps were the same as in Example 2.
[0057] Effect example
[0058] Table 1 below shows the performance analysis results of the anti-aging cables using Examples 1 to 3 of the present invention and Comparative Examples 1 to 7.
[0059] Table 1
[0060]
[0061]
[0062] From the comparison of the experimental data of the embodiment and the comparative example in Table 1, it can be found that the present invention first modifies the graphene oxide to enhance the dispersion performance of the graphene, and mixes it with polyimide in a linear low-density polyethylene matrix, wherein the introduction of nanoparticles improves the compatibility between the two polymer materials, and at the same time can occupy the holes in the matrix, making the structure more stable, thereby enhancing the thermal stability of the cable. At the same time, by enhancing the low expansion performance of the matrix, the sub-microscopic air gaps for water to enter are reduced, thereby reducing the probability of inducing water dendrites, and the short branches on the molecular chain of the linear low-density polyethylene form a large number of entangled molecular chain structures after cross-linking, which are not easy to form water-filled holes under the action of the electric field, thereby inhibiting the further development of water dendrites. Then, the core and the conductor made of the conductive alloy are coated as an insulating material and a sheath material, wherein the insulating layer is subjected to coupled plasma treatment, and a large number of polar oxygen-containing groups are generated on the surface of the matrix to contact the non-polar air environment, thereby causing surface chemical composition reconstruction, so that the matrix can overcome the higher diffusion activation energy at a higher aging temperature, thereby inhibiting the further development of the water dendrites in the cable. After working for a long time, the surface hydrophobicity is achieved through the insulating layer, and the water tree aging resistance of the cable is enhanced. The conductive alloy uses aluminum as a conductive matrix. The aluminum is first borated to ensure the conductivity of the alloy, and then titanium and zirconium are dispersed in the matrix as the second phase. During the solidification process, part of the boron element generates boron-titanium alloy and boron-zirconium alloy, which gradually precipitates and grows from the liquid phase, that is, during the solidification process, the boron element will be enriched at the front of the solid-liquid interface, causing component supercooling, resulting in grain refinement, reducing the thermal expansion of the alloy matrix, thereby improving the water tree aging resistance of the cable. Then, the cavitation effect generated by vibration is used to make the atomic movement of the alloy more intense and sufficient during the smelting process, so that the components in the alloy are evenly diffused, thereby further improving the mechanical properties of the alloy. Next, during the alloy pouring step, the vibration effect is also used to eliminate defects such as holes in conventional casting, improve the mechanical properties of the alloy, and intensify the movement of the alloy during the solidification process, which is helpful to refine the grains of the wire and cable alloy, thereby enhancing the mechanical properties of the alloy and the water tree aging resistance of the cable.
[0063] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. An anti-aging cable, characterized in that: The anti-aging cable is made by coating a core and a conductor made of a conductive alloy with a blend made of modified graphene, polyimide and linear low-density polyethylene as an insulating layer and a sheath layer; a shielding layer is also present between the insulating layer and the sheath layer.
2. The anti-aging cable according to claim 1, characterized in that: The modified graphene is prepared by first subjecting graphene oxide to carboxylation treatment and then grafting polyvinyl alcohol.
3. The anti-aging cable according to claim 1, characterized in that: The conductive alloy is prepared by boronizing aluminum, then adding titanium and zirconium, and then performing ultrasonic treatment.
4. A method for preparing an anti-aging cable, characterized in that: The method comprises the following preparation steps: (1) Mixing graphene oxide with deionized water, ultrasonicating at 21kHz for 40 to 80 minutes, adding sodium hydroxide in an ice-water bath, stirring at 80 to 150 rpm for 30 minutes, adding chloroacetic acid, ultrasonicating at 21kHz for 1.5 to 3 hours, and then centrifugally washing with 1 mol / L dilute hydrochloric acid until the pH of the washing solution is 7 to 8, drying at -24 to -48°C for 25 to 40 hours, and then adding N,N-dimethylformamide, ultrasonicating at 21kHz for 40 to 80 minutes, adding polyvinyl alcohol 1799, and continuing ultrasonicating for 20 to 50 minutes, adding dicyclohexylcarbodiimide and 4-dimethylaminopyridine, stirring at 200 to 400 rpm for 60 to 80 hours, and then placing in a pretreatment dialysis bag for dialysis treatment for 3 to 5 days, replacing deionized water every 12 hours, and finally drying at -24 to -48°C for 25 to 40 hours to obtain modified graphene; (2) Polyethylene DFDA-7042 and polyimide YS20 were mixed, heated to 330-360°C, stirred at 50-100 rpm for 10-40 min, modified graphene, tri-tert-butyl hydroxybenzoate, 2,5-dimethyl-2,5-bis(tert-butyl peroxide)-3-hexyne, and dibutyltin dilaurate were added, stirred for 15-60 min, allowed to stand for 3-6 h, and then heated at 80°C and vacuum for 10 min. -3 Degassing was performed under an environment of 20 minutes, and finally extrusion granulation was performed. The process parameters were as follows: screw diameter was 20 mm, aspect ratio was 25:1, and temperature was 320-400°C to obtain a blend; (3) The aluminum ingot is heated to 750-770°C, and A1-3B master alloy and boron powder are added for boronization. The ingot is stirred at 50-100 rpm for 30-80 min, and the temperature is kept for 10-30 min. The upper two-thirds of the melt is taken, and sponge zirconium and sponge titanium are added. The vacuum degree is drawn to 4.6×10 -3 Pa, then fill with argon to 50MPa, under the state of vibration frequency of 38-50Hz, this vibration state continues until the casting step, heat up to 1900-2200℃ at 5-13℃ / min, keep warm for 5-10min, press hexachloroethane into the bottom of the molten metal to stir, degas and slag, then remove the surface scum, cast the mold, cool and shape, and obtain the conductive alloy; (4) The conductive alloy is drawn into a wire with a diameter of 0.1 to 0.7 mm, coated with the blend with a thickness of 1 to 2 mm, subjected to radio frequency plasma treatment, and then covered with a shielding layer woven of copper wire with a thickness of 0.5 to 2 mm and a protective layer with a thickness of 2 to 5 mm to obtain an anti-aging cable.
5. The method for preparing an anti-aging cable according to claim 4, characterized in that: The preparation method of the pretreatment dialysis in step (1) is as follows: a dialysis bag with a molecular weight cutoff of 12,000 is placed in deionized water at 95° C. and boiled for 10 minutes.
6. The method for preparing an anti-aging cable according to claim 4, characterized in that: The mass ratio of the graphene oxide, deionized water, sodium hydroxide, chloroacetic acid, N,N-dimethylformamide, polyvinyl alcohol 1799, dicyclohexylcarbodiimide and 4-dimethylaminopyridine in step (1) is 1-3:500-1000:50:50:50-80:4-16:0.08-0.18:0.
01.
7. The method for preparing an anti-aging cable according to claim 4, characterized in that: The mass ratio of polyethylene DFDA-7042, polyimide YS20, modified graphene, tri-tert-butyl hydroxybenzoate, 2,5-dimethyl-2,5-bis(tert-butyl peroxide)-3-hexyne, and dibutyltin dilaurate in step (2) is 100:5-20:0.1-0.8:0.05:0.05-0.1:0.04-0.
2.
8. The method for preparing an anti-aging cable according to claim 4, characterized in that: In step (3), the mass ratio of the aluminum ingot, the A1-3B master alloy, the boron powder, the zirconium sponge and the titanium sponge is 10:0.1-0.3:0.03:0.2-1:0.
1.
9. The method for preparing an anti-aging cable according to claim 4, characterized in that: The process parameters of the radio frequency plasma in step (4) are as follows: the gas is oxygen, the flow rate is 0.04-0.1 L / min, the gas pressure is 15-20 Pa, and the power is 150-250 W.
10. The method for preparing an anti-aging cable according to claim 4, characterized in that: The protective layer in step (4) is made of the blend prepared in step (2).